A STUDY ON THE ABILITY OF THE SECOND YEAR STUDENTS OF THE ENGLISH STUDY PROGRAM OF UNIVERSITAS RIAU IN CHOOSING THE CORRECT PREPOSITIONAL PHRASES FOR ADVERB PHRASE - Dewi Lestary; Fakhri Ras; H.M. Nababan ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this descriptive research was to describe the students’ ability in choosing the correct prepositional phrases for adverb phrase. The population of this research was the second year students of the English Study Program of Universitas Riau as big as 86 students of 2014/2015 academic year. Due to the population is very large, which consist of 3 classes, the cluster random sampling technique is used. The whole of number of the population is about 86 students. One of the class is taken as the sample as many as 30 students. The multiple choice test is used to collect the needed data of prepositional phrases for adverb phrase. The collected data were analyzed by calculating the scores of the students in answering the test and classified them to a certain level of ability in choosing the correct prepositional phrases for adverb phrase. The research finding show that the majority of the students passed in choosing the correct prepositional phrases for adverb phrase as big as 90%. This means that the students’ were capable to comprehend the test. The suggestion is that the unsuccessful students should learn more and read about prepositional phrases for adverb phrase. In addition, the teacher should give more explanation about prepositional phrases for adverb phrase for the group of the unsuccessful students.Keywords: ability, choosing, prepositional phrase, adverb, phrase